The unmet needs of women with breast cancer: a qualitative research - Foà, Chiara; Guarnieri, Maria Cristina; Basciu, Valentina; Naldi, Silvia; Scaravella, Mariavittoria; Scirpoli, Antonietta (Acta Biomedica Atenei Parmensis, 2022)
Background and aim of the work.Breast cancer (CM) is the most commonly diagnosed form of cancer in Italy and the most common malignancy in women (25%) with 53,000 new cases. This disease affects all age groups (1 in 40 women